Endonasal FLI Approach for Rhinoplasty with Modified Cottle Low Strip Septoplasty - López-Ulloa, Fausto; Jasso-Ramírez, Elizabeth; Friedman, Oren (Facial Plastic Surgery, 2021)
To date, an endonasal approach has not been described that combines different incisions to provide exposure of all of the key anatomical structures, allowing for adequate, comprehensive visualization of the nasal architecture including the complete quadrangular cartilage and its extension with the upper lateral cartilages, including the caudal septal border from the ventral border and anterior nasal spine to the anterior septal angle, the scroll, and internal nasal valve.The endonasal approach that Fausto Lopez-Infante designed, the FLI technique, combines several basic known endonasal incisions that together allow excellent access and great visualization of the intranasal surgical field, enables extensive septal work, and preserves the natural anatomy of the dorsum as well as the tip support structures.This technique and approach to nasal surgery are based on an understanding of anatomy, allow standardization of the surgery, and make it reproducible. It is an outstanding option with excellent cosmetic and functional results.
Keywords: FLI approach; endonasal approach; septorhinoplasty; technique; nasal anatomy